Computerized assessment of competence‐related abilities in living liver donors: the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study. (16th July 2013) - Freeman, Jason; Emond, Jean; Gillespie, Brenda W.; Appelbaum, Paul S.; Weinrieb, Robert; Hill‐Callahan, Peg; Gordon, Elisa J.; Terrault, Norah; Trotter, James; Ashworth, April; Dew, Mary Amanda; Pruett, Timothy; et al.
Abstract Background Despite its importance, determination of competence to consent to organ donation varies widely based on local standards. We piloted a new tool to aid transplant centers in donor assessment. Methods We assessed competence‐related abilities among potential living liver donors (LDs) in the nine‐center A2ALL study. Prospective LDs viewed an educational video and were queried to assess Understanding, Appreciation, Reasoning, and ability to express a Final Choice using the MacArthur Competence Assessment Tool for Clinical Research, adapted for computerized administration in LDs ("MacLiver"). Videotaped responses were scored by a clinical neuropsychologist (JF). Results Ninety‐three LDs were assessed. Mean (standard deviation; domain maximum) scores were as follows: Understanding: 18.1 (2.6; max = 22), Appreciation: 5.1 (1.0; max = 6), Reasoning: 3.1 (0.8; max = 4), and Final Choice: 3.8 (0.5; max = 4). Scores did not differ by demographics, relationship to the recipient, eligibility to donate, or eventual donation (p > 0.4). Higher education was associated with greater Understanding (p = 0.004) and Reasoning (p = 0.03). Conclusion Standardized, computerized education with independent ratings of responses may (1) alert the clinical staff to potential donors who may not be competent to donate and (2) highlight areas needing further assessment and education, leading to better informed decision making.